Insights and Field-level experiences of Non-Performing Loans in Bangladesh: The Case of State-Owned Commercial Banks (SOCBs) - Hasan, Md Nazmul; Khan, Sadia Noor (Dhaka University Journal of Business Studies, 2023)
The banking industry of Bangladesh has been facing the most turbulent times of its history due to myriad forms of challenges. The crippling scenario has been contributed by multifarious reasons among others, corrupt loan practices and connected-party lending (i.e., lending to board members’ firm), lack of monitoring, supervision and inefficiencies of board members especially in state-owned commercial banks, monopolization of banks by certain industrialist groups, unprecedented political interferences and non-existent punitive measures for miscreants by the highest regulatory body i.e., Bangladesh Bank. All these reasons coupled with recent implication of single-digit interest rate are putting the banking industry into vulnerable state and thereby losing the trust and confidence of the mass-people. The excessive volume of NPL will possibly jeopardize the profitability of banks and erode the accumulated capital which might lead to the systematic risks of bank failures in the days to come. To this backdrop, the authors intend to shed some lights with a deeper look on the origin and effects of NPL based on a sample of 200-survey respondents and endeavored to explore industry-insights which might be of special interests to bank owners, managements bodies, regulator i.e., Bangladesh Bank (BB) and finally the shareholders. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 151-174